2011
DOI: 10.1111/j.1365-2982.2011.01677.x
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid‐induced delayed gastric emptying is selectively increased upon intermittent administration in the rat: role of CB1 receptors

Abstract: Upon intermittent administration, hypersensitization may develop to some effects (particularly delayed gastric emptying) induced by cannabinoid agonists. CB1 antagonists/inverse agonists may show different efficacy upon repeated or single administration to block cannabinoid-induced central and gastrointestinal effects. Thus, cannabinoid effects are dependent on the pattern of drug administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 37 publications
7
43
1
Order By: Relevance
“…CS-MetFr and CS-ButFr did not show any significant protection against cisplatin-induced vomiting. Cannabinoids have been reported to cause the suppression of GIT motility (Abalo et al, 2011), as it causes the inhibition of ongoing contractile transmitter release (Pertwee, 2001b). It is hypothesized that this suppression may antagonize the antiemetic activity as cisplatin is causing delay in gastric emptying per se.…”
Section: Discussionmentioning
confidence: 99%
“…CS-MetFr and CS-ButFr did not show any significant protection against cisplatin-induced vomiting. Cannabinoids have been reported to cause the suppression of GIT motility (Abalo et al, 2011), as it causes the inhibition of ongoing contractile transmitter release (Pertwee, 2001b). It is hypothesized that this suppression may antagonize the antiemetic activity as cisplatin is causing delay in gastric emptying per se.…”
Section: Discussionmentioning
confidence: 99%
“…This somehow unexpected finding made us study the modifications induced by acute and repeated cisplatin on GI motility by radiographic means and found that: pica and delayed gastric emptying were temporally related [51]; the repeated administration of cisplatin induced a parallel increase in both pica and delayed gastric emptying [52]. As mentioned above, upon WIN intermittent administration (4 intraperitoneal injections, 1/week), which was the pattern of administration applied in the mentioned pica study [50], delayed gastric emptying was also intensified [31]. It is likely that the lack of effect of WIN on pica behaviour induced by cisplatin has something to do with the fact that both drugs delayed gastric emptying in the rat, and likely added their effects on the GI tract.…”
Section: Cb Effects On Altered Gi Motilitymentioning
confidence: 99%
“…Upon daily administration, tolerance developed to WIN effects in the small and large intestine, but not in the stomach [29]. However, upon intermittent administration, the gastric effect of WIN was enhanced to the point that it did not allow for a proper separate analysis of motility in the small and large intestines [31]. Therefore, the stomach shows peculiar responses to CB acute and chronic treatments.…”
Section: Cannabinoids Reduce Gastrointestinal Motor Functionmentioning
confidence: 99%
See 2 more Smart Citations